Nutritional Status of Children Under Five Years in Hassan Sham Camp in Mosul City in Iraq - Ayad Abdullah Rasheed; Salih Ahmid Abdullah; Nasih Abdulla Hossain Gardi (Zanco Journal of Pure and Applied Sciences, 2020)
Background and objective: Adequate nutrition is essential in early childhood to ensure healthy growth, proper organ formation and function, a strong immune system, and neurological and cognitive development. Economic growth and human development require well-nourished populations who can learn new skills, think critically and contribute to their communities (WHO, 2010). The aim of study was to identify nutritional status of children under five years old in Hasan Sham camps in Mosul City in Iraq. Methods: Quantitative design, cross-sectional descriptive study has been conducted to assess the health status of children under five years in Hasan sham camps Mosul City. The data were collected in July, 2017. So 322 children were chosen randomly out of 1300 children under five years old age. For the purpose of data collection, a questioner was designed according the needs of study that contained three part. Part one included questioner related to demographic characteristics, Part two included type of feeding, Part three contain Anthropometric measurement, Data were collected through using modified questionnaires was designed through extensive review of relevant literature. Results: the study revealed that percentage of health problems was as followings: Chronic underweight 4%, Chronic stunting8%, Acute stunting 22%, Chronic wasting 1%, Acute wasting 7%. Conclusion: study revealed that theirs not association between age groups and underweight, stunting, and wasting among children. And there is not association between gender and underweight, stunting, and wasting among children. Keywords: Nutritional status, Hassan Sham Camp.